2019
DOI: 10.1111/jcmm.14622
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin inhibits adipogenesis of tendon stem cells and lipids accumulation in rat injury tendon through regulating PTEN/PI3K/AKT signalling

Abstract: Tendon injury repairs are big challenges in sports medicine, and fatty infiltration after tendon injury is very common and hampers tendon injury healing process. Tendon stem cells (TSCs), as precursors of tendon cells, have shown promising effect on injury tendon repair for their tenogenesis and tendon extracellular matrix formation. Adipocytes and lipids accumulation is a landmark event in pathological process of tendon injury, and this may induce tendon rupture in clinical practice. Based on this, it is impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…TSPCs were isolated and identified, as previously reported by the investigators [ 16 , 22 ]. Briefly, the Achilles tendon tissue was collected from three male 4-week-old Sprague Dawley (SD) rats (provided by the Animal Center of Third Military Medical University) after being euthanized.…”
Section: Methodsmentioning
confidence: 99%
“…TSPCs were isolated and identified, as previously reported by the investigators [ 16 , 22 ]. Briefly, the Achilles tendon tissue was collected from three male 4-week-old Sprague Dawley (SD) rats (provided by the Animal Center of Third Military Medical University) after being euthanized.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the phosphorylation of AKT was significantly elevated after HUMSC-Exos treatment and act as the upstream inducing event for mTOR phosphorylation, whereas miR-29a antagonist produced the opposite results. In line with these results, PTEN/AKT signaling was also reported to be closely related to the TDSCs senescence and tendon atrophy [ 63 ], while decreasing PTEN/AKT signaling yielded benefits for inhibiting TDSCs adipogenesis and tendon fatty infiltration [ 64 ]. Thus, our results in this study collectively proposed that HUMSC-Exos might enhanced the tenogenic potential of TDSCs through modulating PTEN/AKT/mTOR pathway by transferring miR-29a.…”
Section: Discussionmentioning
confidence: 79%
“…Current studies have confirmed that EMT accompanied by high expression of PI3K, AKT and mTOR proteins occurs in PMCs under the stimulation of high-glucose dialysate (Deng et al, 2019). A study by Wang et al (2019) found that there is excessive activation of AKT in peritoneal EMT tissue, suggesting that the PI3K/AKT signalling pathway is involved in the EMT process of peritoneal tissue. After treatment with the PI3K/AKT pathway blocker wortmannin, the expression of p-AKT and α-SMA in PMCs was significantly inhibited (He et al, 2020).…”
Section: Discussionmentioning
confidence: 80%